The Effect of Using Tree Diagram Technique for Improving Students’ Vocabulary Mastery - Olyvia Revalita Candraloka; Ani Novitasari (UIR Press, 2022)
This study was aimed to examine the effectiveness of using the Tree Diagram technique to enhance mastery of vocabulary in seventh-grade students of MTs Miftahul Huda Bulungan in the academic year 2021/2022. Quasi-experimental with non-equivalent control group design was used as the research design. The sampling technique used was purposive sampling and involved two classes which included 33 students in the experimental group and 32 students in the control group. The instruments were 20 multiple-choice questions and 5 essay questions. A T-test was used to analyze the data. The result of the t-test was 2,786>1,670. The Null Hypothesis (Ho) was rejected. There was a significant difference in mean scores of pretest and posttest which indicated that the tree diagram technique took a good effect on the students’ vocabulary mastery. This study concluded that the implementation of the tree diagram was effective to improve the students’ vocabulary mastery